COMPUTER MODELING OF RADIO FREQUENCY SATELLITE TRANSPONDER FOR TRANSMISSION OF ADS-B MESSAGES SATELLITE COMMUNICATION CHANNEL - Kharchenko, Volodymyr; Bo, Wang; Grekhov, Andrii; Stahovskyi, Petro (Proceedings of National Aviation University (archive), 2014)
For investigation of ADS-B messages transmission via radio frequency satellite link the original model ofa communication channel "Aircraft-to-Satellite-to-Ground Station" was built using MATLAB Sіmulіnk. Model consistsof aircraft transmitter, uplink/downlink path, satellite transponder, ground station receiver. BER dependencies on FreeSpace Path Losses, Noise Temperatures and Satellite Transponder Amplifier Gain were received and analyzed.